ANALISIS KOMPARATIF LEMBAGA PENYELENGGARA PEMILU: ELECTION COMMISSION OF INDIA DAN AUSTRALIAN ELECTORAL COMMISSION (Jurnal Nawala Politika, 2023)
The holding of general elections requires an independent electoral management body and is supported by clear and strong constitutional legitimacy. This is so that the elections held can achieve democratic general elections. The implementation of general elections in a democratic country will be a benchmark for democracy in that country. The discussion through comparative analysis will explain the similarities and differences in the election management bodies in India and Australia, namely the Election Commission of India (ECI) and the Australian Electoral Commission (AEC)